Different Abilities of Thrombin Receptor Activating Peptide and Thrombin to Induce Platelet Calcium Rise and Full Release Reaction - Lasne, Dominique; Donato, José; Falet, Hervé; Rendu, Francine (Thrombosis and Haemostasis, 1995)
Synthetic peptides (TRAP or Thrombin Receptor Activating Peptide) corresponding to at least the first five aminoacids of the new N-terminal tail generated after thrombin proteolysis of its receptor are effective to mimic thrombin. We have studied two different TRAPs (SFLLR, and SFLLRN) in their effectiveness to induce the different platelet responses in comparison with thrombin. Using Indo-1/AM- labelled platelets, the maximum rise in cytoplasmic ionized calcium was lower with TRAPs than with thrombin. At threshold concentrations allowing maximal aggregation (50 μM SFLLR, 5 μM SFLLRN and 1 nM thrombin) the TRAPs-induced release reaction was about the same level as with thrombin, except when external calcium was removed by addition of 1 mM EDTA. In these conditions, the dense granule release induced by TRAPs was reduced by over 60%, that of lysosome release by 75%, compared to only 15% of reduction in the presence of thrombin. Thus calcium influx was more important for TRAPs-induced release than for thrombin-induced release. At strong concentrations giving maximal aggregation and release in the absence of secondary mediators (by pretreatment with ADP scavengers plus aspirin), SFLLRN mobilized less calcium, with a fast return towards the basal level and induced smaller lysosome release than did thrombin. The results further demonstrate the essential role of external calcium in triggering sustained and full platelet responses, and emphasize the major difference between TRAP and thrombin in mobilizing [Ca2+]j. Thus, apart from the proteolysis of the seven transmembrane receptor, another thrombin binding site or thrombin receptor interaction is required to obtain full and complete responses.